PENERAPAN METODE GERAKAN OBYEK UNTUK PENGAMBILAN CITRA DIGITAL PADA OBTION REMOTE VERSI 1.0 - Astika Ayuningtyas; Agus Basukesti; NurCahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2012)
Development of the world's information and communication technology-based growing rapidly. The development of these technologies has given rise to another dimension in human life, namely the need for computer use. Application of machine vision applications where a computer has the ability to understand the data in the form of image and make decisions based on data obtained from a real object, in this case is generated through the capture image from webcam. The images (digital images) of a real object through a webcam can be done in many ways capture the object. In this research object retrieval using an object of activity is captured on the webcam through the motions of objects. Digital image acquisition is performed with the tool in the form of software (Obtion Remote Version 1.0). Obtion (Object Detection) method works with the system of comparison between that time frame the previous frame captured by the camera at the time of recording the object. Comparison of the difference in the frame will be accommodated in a place that will be used to support the execution of an object by counting the number of pixels that exceed the value of the difference in number of field values with regulator frame to frame changes in the location of the object motionObtion Remote Version 1.0 will take a digital image of the object with trigger object motion detection performed. Digital image acquisition (capture the object with a webcam) will be done automatically if the object has been successfully detected. The detected object will be stored automatically in the directory are executed as a digital image storage.